2020
DOI: 10.1002/app.49213
|View full text |Cite
|
Sign up to set email alerts
|

Tensile testing and fracture mechanism analysis of polyvinyl alcohol nanofibrous webs

Abstract: A tensile properties testing study was conducted to understand the influence of thickness, cross-head speed (speed of testing), gauge length (GL; specimen test length), and sample shape on important tensile properties of polyvinyl alcohol (PVA) nanofiber webs. The effects of each testing parameter on load at break, extension at break, Young's modulus, and tensile stress-strain curve of PVA nanofiber webs are analyzed. The Welch two sample t-tests show the significant difference among tested data. Using interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…This because of the increased bonding structure and fiber nodes. These testing results matched the mechanism with our previous results about nanofiber webs [18]. This study's mechanisms of testing speed, angle to machine direction, and specimen width are not clear due to the multifactor experiment.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This because of the increased bonding structure and fiber nodes. These testing results matched the mechanism with our previous results about nanofiber webs [18]. This study's mechanisms of testing speed, angle to machine direction, and specimen width are not clear due to the multifactor experiment.…”
Section: Resultssupporting
confidence: 88%
“…As is shown in Table 4, the R 2 of most regression equations is around 0.8 ( L : 0.83, Ex : 0.85, Sa : 0.77, M : 0.88, En : 0.85), which means that there is a strong positive relationship between testing parameters or sample characteristics and tensile results; therefore, the parameters have obvious influence on these five tensile properties. Comparatively, the R 2 of tensile stress is 0.70, which is much lower than the other R 2 ; a study by Lou et al 17, 18 showed that an R 2 of 0.70 possibly indicates the influence of interactive effects or inherent fiber factors (e.g. molecular weight or viscosity).…”
Section: Resultsmentioning
confidence: 89%
“…This is attributed to its elastomeric behavior at room temperature due to its low glass transition temperature ( T g = −60°C) 43 . This mechanical behavior allows electrospun films to have an elastic modulus compared to the skin 44–46 . In previous studies developed in our group, 47 the preservation of the main structure of type I collagen (triple helix) was observed in Col_1/poly(vinyl alcohol) (PVA) electrospun monolithic nanofibers when an acid solvent system composed of acetic acid/ultrapure water was used.…”
Section: Introductionmentioning
confidence: 94%
“…43 This mechanical behavior allows electrospun films to have an elastic modulus compared to the skin. [44][45][46] In previous studies developed in our group, 47 the preservation of the main structure of type I collagen (triple helix) was observed in Col_1/poly(vinyl alcohol) (PVA) electrospun monolithic nanofibers when an acid solvent system composed of acetic acid/ultrapure water was used. However, it was seen that monolithic fibers were solubilized after a few hours in contact with saline solution.…”
mentioning
confidence: 95%
“…Methods described by Turaga et al (2016) and Lou et al (2020) were used in the present study with slight modifications. Briefly, multiple 10% PVA solutions (w/v) were prepared by dissolving 5 g of PVA in 45 mL deionized water at 80°C for 3 h with intermittent stirring.…”
Section: Methodsmentioning
confidence: 99%